Revisiting Radio Variability of the Blazar 3C 454.3 - Ashutosh Tripathi; Alok C. Gupta; Krista Lynne Smith; Paul J. Wiita; Margo F. Aller; Alexandr E. Volvach; Anne Lähteenmäki; Hugh D. Aller; Merja Tornikoski; Larisa N. Volvach (The Astrophysical Journal, 2024)
We examine lengthy radio light curves of the flat spectrum radio galaxy 3C 454.3 for possible quasiperiodic oscillations (QPOs). The data used in this work were collected at five radio frequencies, 4.8, 8.0, 14.5, 22.0, and 37.0 GHz between 1979 and 2013 as observed at the University of Michigan Radio Astronomical Observatory, Crimean Astrophysical Observatory, and Aalto University Metsähovi Radio Observatory. We employ generalized Lomb–Scargle periodogram and weighted wavelet transform analyses to search for periodicities in these light curves. We confirm a QPO period of ∼2000 days to be at least 4 σ significant using both methods at all five radio frequencies between 1979 and 2007, after which a strong flare changed the character of the light curve. We also find a ∼600 day period, which is at least 4 σ significant, but only in the 22.0 and 37.0 GHz light curves. We briefly discuss physical mechanisms capable of producing such variations.